The linguistic signifier: from corporeality to (micro)networks: Introduction in English - Grégoire, Michaël (Signifiances (Signifying), 2023)
This introduction starts from the observation that the signifier, especially in the field of enaction and embodied cognition, only takes into account certain aspects of the emergence of cognition linked to language as a result of lived interactions. Indeed, it does not take sufficiently into account the fact that the linguistic signifier, besides being the product of a bodily act, has an eminently systemic and cultural dimension. The question raised here is to reconcile the reticular dimension of the signifier and its bodily dimension.